Narratives of Orthopedic Residents on Vicarious Trauma: A Narrative Analysis of Therapeutic Meaning Reconstruction - Aminian, Amir; Shakeri, Mohamadreza; Moeini, Javad; Shokatpour Lotfi, Shahla (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The present study was conducted to explore and understand the lived experiences of orthopedic residents in confronting vicarious trauma and to elucidate the process of meaning reconstruction among them. Methods and Materials: This study was conducted using a qualitative approach and descriptive phenomenological methodology. Five orthopedic residents working at the Bone and Joint Reconstruction Research Center of Shafa Yahyaeian Hospital were selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using Colaizzi’s seven-step method. To ensure scientific rigor, Guba and Lincoln’s criteria, including credibility, transferability, dependability, and confirmability, were employed. Findings: Data analysis resulted in the identification of five main thematic clusters: (1) cumulative systemic burden (burnout and structural injustice); (2) confrontation with therapeutic trauma (patient death and violence); (3) emotional and coping reactions (emotional numbness and anger); (4) reconstruction of professional meaning (therapeutic efficacy and family support); and (5) professional identity at the crossroads (doubt and a dual future). The findings demonstrated that trauma among orthopedic residents is a cumulative process that begins with systemic pressure and leads to a rupture in meaning; however, through intrinsic resources and feedback from patient recovery, processes of meaning reconstruction and vicarious resilience ultimately emerge. Conclusion: Orthopedic residents encounter traumatic moments within a context of limited organizational support that challenges their framework of meaning. Nevertheless, the enduring core of their professional identity is preserved through spontaneous meaning-making processes.